Comparison of powdered enamel sample pretreatment methods for strontium isotope analysis - Crowley, Brooke Erin; Bruff Simpson, Emily Michelle; Hammer, Sarah Jayne; Smith, Joshua Michael; Johnson, Thomas Martin (Frontiers in Environmental Chemistry, 2023)
Most researchers assume minimal impact of pretreatment on strontium isotope ratios (87Sr/86Sr) for bones and teeth, and methods vary tremendously. We compared 14 pretreatment methods, including no prep other than powdering enamel, ashing, soaking in water, an oxidizing agent (bleach or hydrogen peroxide) or acetic acid (0.1M, 1.0M, and 1.0M buffered with calcium acetate), and a combination of these steps. We prepared and analyzed aliquots of molar enamel from three proboscideans (one modern captive Indian elephant, Elephas maximus indicus; one Pleistocene mastodon, Mammut americanum; and one Miocene gomphothere, Afrochoerodon kisumuensis). Each pretreatment was performed in triplicate and we measured 87Sr/86Sr, Sr concentration, and uranium (U) concentration, using the same lab space and instrumentation for all samples. Variability in 87Sr/86Sr and Sr and U concentrations was considerable across pretreatments. Mean 87Sr/86Sr across methods ranged from 0.70999 to 0.71029 for the modern tooth, 0.71458 to 0.71502 for the Pleistocene tooth, and 0.70804 to 0.70817 for the Miocene tooth. The modern tooth contained the least Sr and negligible U. The Pleistocene tooth contained similar amounts of Sr and measurable amounts of U, and the Miocene tooth had approximately 5x more Sr and U than the Pleistocene tooth. For all three teeth, variance in 87Sr/86Sr, Sr concentrations, and U concentrations was statistically indistinguishable across pretreatments, but there were apparent differences among pretreatments for the modern and Pleistocene teeth. Both contained relatively little Sr, and it is possible that small amounts of exogenous Sr from reagents, building materials or dust affected some replicates for some pretreatments. Variability in median 87Sr/86Sr across pretreatments for the modern and Pleistocene teeth was considerable. For the Miocene tooth, overall variability in 87Sr/86Sr was much smaller, but there were significant differences among pretreatments. Most yielded 87Sr/86Sr and Sr concentrations comparable to, or lower than, untreated powder, suggesting selective removal of exogenous material with high 87Sr/86Sr. Further evaluation of the mechanisms driving isotopic variability among pretreatment methods is warranted. Researchers should clearly report their methods and avoid combining data obtained using different methods. Small differences in 87Sr/86Sr could impact data interpretations, especially in areas where isotopic variability is low.